BEAUTY OF WOMEN FROM IDEAL APPEARANCE AND UNDERSTANDING OF BEAUTY STANDARDS: A LITERATURE REVIEW - Sari, Mila; Ayuningtyas, Chandra Dyah; Cristin, Sarah; Rahyadi, Irmawan (Sean Institute, 2022)
Women's beauty is crucial for women as identification of beauty with interesting things about the desire to meet needs and satisfaction in appearance from a different perspective. This study uses content analysis of a number of articles that will focus on sources of data from Scopus-indexed journals with a focus on discussing women's beauty from various findings that have been published in the SAGE Journals, Taylor & Francis and Wiley database with the main focus of research being critical thinking skills from inclusion and exclusion criteria. Narrative literature reviews the perspective of ideal appearance and understanding of beauty standards as factors for identifying women's beauty. The current study reveals that in the last six years, female beauty has highlighted the perspective of ideal appearance with aspects of the influence of social media exposure on women's behaviour, body dissatisfaction to appearance and body care trends which are dominated by the effects of using social media Instagram. While different understandings influence the perspective of beauty standards in the construction of beauty in the perspective of social interaction, body image to ethnicity and minorities.